Community-based disaster risk reduction - Shaw, Rajib (Community, environment and disaster risk management ;, 2012)
Communities are at the core of disaster risk reduction (DRR), and community based approaches are getting increasing focus in national DRR plans. In the case of past disasters, communities were always the first responders, and took leading roles in the post disaster recovery. The roles of communities in pre-disaster preparedness are also very important. This is the first comprehensive book available on CBDRR (community based disaster risk reduction) which outlines both research and practice, citing field examples and research results. It provides an overview of the subject and looks at the role of governments, NGOs, academics and corporate sectors in community based disaster risk reduction. It proceeds to examine experiences from Asian and African countries, and concludes by looking ahead to the future perspective of CBDRR.